2010
DOI: 10.1177/153567601001500204
|View full text |Cite
|
Sign up to set email alerts
|

Does That Face Mask Really Protect You?

Abstract: MethodDust storm aerosol concentrations and particle size distributions have been measured in many countries. The mean aerosol concentration of a moderate dust storm is 0.040 mg/L, and the particle size is less than or equal to 2.5 m (Chan, 2002;Selinus, 2005). Therefore, the test plenum target aerosol concentration was 0.40 mg/L and the target particle size was 1.0 to 2.5 m. Although this particle size range is larger than the actual geometric diameter of viral particles (approximately 0.02 to 0.2 m), it shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 3 publications
1
38
0
Order By: Relevance
“…In NIOSH testing, average decreases in exposure while wearing surgical masks ranged from 15 to 40% depending on the mask used [97]. A similar study testing fine NaCl particle exposures with manikins found that the surgical mask decreased exposure 33% on average [95]. An evaluation of surgical masks under actual breathing conditions, using a panel of healthy adults meant to imitate the NIOSH respirator testing panel, demonstrated that of the NaCl test particles in the environment,~30% leaked in around the edges of a surgical mask and 5-8% came through the mask (Fig.…”
Section: Data Regarding the Use Of Non-respirator Masksmentioning
confidence: 99%
See 1 more Smart Citation
“…In NIOSH testing, average decreases in exposure while wearing surgical masks ranged from 15 to 40% depending on the mask used [97]. A similar study testing fine NaCl particle exposures with manikins found that the surgical mask decreased exposure 33% on average [95]. An evaluation of surgical masks under actual breathing conditions, using a panel of healthy adults meant to imitate the NIOSH respirator testing panel, demonstrated that of the NaCl test particles in the environment,~30% leaked in around the edges of a surgical mask and 5-8% came through the mask (Fig.…”
Section: Data Regarding the Use Of Non-respirator Masksmentioning
confidence: 99%
“…Similarly, a study that evaluated commercially available cloth masks found that the filtration efficiency for ultrafine diesel particles ranged from 10 to 80% depending on the size of the particle and the type of mask [94]. A bandana secured to a manikin reduced fine particulate sized saline aerosol by only 10% on average [95]. So while impressive reductions may theoretically be possible with masks from other materials, it would be unreasonable to expect those sorts of reductions consistently in the real world, unless a regulatory body were to start testing and providing standards for these mask types.…”
Section: Data Regarding the Use Of Non-respirator Masksmentioning
confidence: 99%
“…According to research, surgical masks, pre-shaped dust masks, and bandanas offer very little protection (Bowen, 2010) against aerosolized infection. This was also shown in a study in Asia in a health care environment where more than 1,900 hospital workers were asked to wear surgical masks, fit-tested or not fit-tested N95 respirators, or no respirators (MacIntyre, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Mask use, chiefly with a pañuelo, a cloth bandana covering the mouth and nose, is primarily reported by women, here and in other studies (28). Cloth bandanas are of limited effectiveness for respiratory protection (29), and educational campaigns should focus on limiting work under dusty conditions and promoting use of National Institute for Occupational Safety and Health (NIOSH)-approved respirators with particulate filters rated N95, N99, N100, P100, or HEPA when such work is necessary. Unfortunately, compliance may be reduced by the practical challenges of using personal respiratory protection, including discomfort and interference with speed and workflow.…”
Section: Discussionmentioning
confidence: 65%